(untitled) (Perner’s Contacts, 2014)
The paper is aimed on the definition of global navigation satellite system and inertial navigation system. INS is explained on the basis of the reference frame, complete with illustrations for better understanding. GNSS explains the communication among the three segments, namely management, user and space. Integration between systems may have been transferred by three integration methods. In conclusion, the article is assessed contribution navigation systems in technical and industrial sectors.